Youth culture in modern Britain, c. 1920 - c. 1970: from ivory tower to global movement – a new history - Fowler, David (Palgrave Macmillan, 2008)
This book traces the history of youth culture from its origins among the student communities of inter-war Britain to the more familiar world of youth communities and pop culture. Grounded in extensive original research, it explores the individuals, institutions and ideas that have shaped youth culture over much of the twentieth century.